Chemical Diagnosis of Renal and Hepatic Function: Current Approaches and Future Perspectives - Esraa Wisam Jawad Kazim; Zahraa Asaad Mahmood Shaker; Ayat Bashir Hathoot Dhafal; Ahmed Saleh Mahdi Sabih; Ahmed Faleh Hassan Sadiq; Ahmed Basim Khalaf Saleh (American Journal of Biomedicine and Pharmacy, 2025)
The chemical diagnosis of renal and hepatic function is essential for assessing organ health, detecting pathologies, and monitoring disease progression. Despite advances in biochemical assays, limitations in sensitivity and specificity highlight the need for improved diagnostic methodologies. This study explores traditional and emerging biomarkers for evaluating kidney and liver function, emphasizing novel diagnostic technologies. A literature review was conducted to analyze biochemical parameters such as blood urea nitrogen (BUN), creatinine, and liver enzymes (ALT, AST, ALP), alongside new biomarkers and bioanalytical techniques. Findings suggest that integrating precision diagnostics and biomarker profiling enhances early disease detection and clinical decision-making. Results indicate that advancements in biosensors, proteomics, and AI-driven diagnostics hold promise for improving renal and hepatic assessments. These developments have significant implications for personalized medicine, allowing for more accurate and timely interventions in renal and hepatic disorders.